PEMBELAJARAN CERAMAH DENGAN MEDIA ANIMASI UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MEMBACA GAMBAR PROYEKSI - Anam, Choirul; Khumaedi, Muhammad; Basyirun, - (Jurnal Pendidikan Teknik Mesin, 2009)
Ability reads projection drawing is space shadow three dimensions becomes twodimensions, for the purpose usage of animation media in study of technical drawing it isof course will be able to assist fantasy (imagination) student to the shadow. As for thisresearch aim to know ability of student in reading projection drawing, are theredifference signifikan between the ability, and how much level of improvement of abilitybetween hit by study of discourse equiped by animation media and study of ordinarydiscourse. To express ability of student is applied by double alternative form test methodwith four alternative of answer (option). This research takes population of all classstudent 2nd expertise program of keeping engineering of industrial mechanic of SMKDr. Tjipto Semarang school year 2009/2010. Determination of group of treatment appliessample random/ is balloted. Result of data analysis indicates that improvement of abilityof group of higher experiment from at group of control and existence of differencesignifikan ability of student in reading projection drawing between both the groups.From result of this research, suggested to all drawing teacher technique in better applystudy method of discourse equiped by animation media alternatively when teachingocular diklat to read projection drawing discussion fundamental engineering drawing.Kata kunci: gambar proyeksi, kemampuan, media animasi.